2021
DOI: 10.1093/neuonc/noab196.725
|View full text |Cite
|
Sign up to set email alerts
|

Qolp-04. The Ketogenic Diet Plus Standard Care for Recently Diagnosed Glioblastoma: A Phase 1 Safety and Feasibility Trial

Abstract: INTRODUCTION There is abundant interest in the potential therapeutic and supportive role of a ketogenic diet (KD) for glioblastoma patients. We conducted a single-arm phase 1 trial to assess the safety and feasibility of KD plus standard-of-care (SOC) in glioblastoma patients (NCT03451799). METHODS Adults within 3 months of diagnosis participated in a 16-week intervention of a classic 3:1 KD (grams fat : grams carbohydrate + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They analyzed survival only for patients who were at least two years from diagnosis; among patients with GBM (n=15), only four met the two-year survival criteria, which was consistent with existing non-KMT literature in which patients were treated using the standard of care. Hu et al recently published a small phase 1 trial that showed safety and markedly favorable responses in some patients [ 25 ]. Despite these findings, no thorough studies have been published on KMT among patients with glioma.…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed survival only for patients who were at least two years from diagnosis; among patients with GBM (n=15), only four met the two-year survival criteria, which was consistent with existing non-KMT literature in which patients were treated using the standard of care. Hu et al recently published a small phase 1 trial that showed safety and markedly favorable responses in some patients [ 25 ]. Despite these findings, no thorough studies have been published on KMT among patients with glioma.…”
Section: Introductionmentioning
confidence: 99%